Analysis of the Significance Value of the Muara Tembesi Old Town Area Based on Law No. 11 of 2010 as a Cultural Preservation Effort - Wulan Resiyani Wulan Resiyani; Agmeysa Rizqi Yudiseconda (Jurnal Kewarganegaraan, 2026)
This research is entitled "Analysis of the Important Value of the Muara Tembesi Old Town Site Area. The Muara Tembesi Old Town Site area is located in Pasar Tembesi Village, Muara Tembesi, Batang Hari Regency, Jambi Province. This research was conducted to determine the important values contained in the Muara Tembesi Old Town Site Area. The method used in this research is a qualitative method. The stages carried out in this research were data collection, namely literature study, observation and interviews, data processing was carried out by means of data identification and classification. Next, data analysis was carried out. The results of this research show that the Muara Tembesi Old City Site Area has five important values, namely Historical Important Value, namely the events of the Rajo Batu war and the 1949 transfer of sovereignty event, Scientific Important Value, based on archeology, history, architecture and civil engineering, Scientific Value. Important Education which can be seen from archaeological remains which have the potential to become a medium of education for future generations, Important Economic Value seen from the use of archaeological remains which are still used today as a source of community economy and Important Cultural Value which is public and political.